How and Why Teachers Taught About the 2020 U.S. Election: An Analysis of Survey Responses From Twelve States - Paul G. Fitchett; Brett L. M. Levy; Jeremy D. Stoddard (SAGE Publishing, 2024)
This study explores social studies teachers' self-reported instruction about teaching the 2020 election in U.S. secondary schools. We analyzed survey responses from 1,723 secondary social studies teachers from 12 states (3 left-leaning, 3 right-leaning, 6 battleground) collected in the weeks after the election, examining self-reported pedagogies, topics taught, and overall frequency of teaching about the election. Respondents reported teaching about the election more frequently if they taught courses in civics or government and/or if they had greater control over their curricula. Analyses indicated that teachers' demographic characteristics, teaching contexts, and ideologies about civic education were related to the election-related topics they taught and the instructional practices they employed. Our findings have important implications for educators, administrators, policymakers, and others interested in strengthening civic learning.